PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TEKNIK BERKIRIM SALAM DAN SOAL DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 BASA AMPEK BALAI KABUPATEN PESISIR SELATAN - Welita, Rida; Aima, Zulfitri; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research was conducted based on the fact that the studentsâ understanding on mathematics concept was still low and the students seemed unable to answer the questions given by the teacher. This research was aimed atrevealing whether the use of Chained-Greeting and Question technique accompanied with Handout could improve the second year studentsâ understanding on mathematics concept better than that of conventional learning. The population of the research was the second year students of SMPN 3 Basa Ampek Balai. The data was collected through a post-test that used mathematics conceptual understanding indicators and scoring based on analytic rubric. The data gotten was analyzed by using t-test assisted with MINITAB. The result of this analysis showed that P-Value was 0.001 which was smaller than Î±=0.05 indicating that hypothesis was accepted. In conclusion, it can be said that that the use of Chained- Greeting and Question technique accompanied with Handout could improve the second year studentsâ understanding on mathematics concept better than that of conventional learning at SMPN 3 Basa Ampek Balai in Academic Year 2013-2014.